Targeting cyclin-dependent kinases in sarcoma treatment: Current perspectives and future directions - Merlini, Alessandra; Pavese, Valeria; Manessi, Giulia; Rabino, Martina; Tolomeo, Francesco; Aliberti, Sandra; D’Ambrosio, Lorenzo; Grignani, Giovanni (Frontiers in Oncology, 2023)
Effective treatment of advanced/metastatic bone and soft tissue sarcomas still represents an unmet medical need. Recent advances in target therapies have highlighted the potential of cyclin-dependent kinases (CDK) inhibitors in several cancer types, including sarcomas. CDKs are master regulators of the cell cycle; their dysregulation is listed among the “hallmarks of cancer” and sarcomas are no exception to the rule. In this review, we report both the molecular basis, and the potential therapeutic implications for the use of CDK inhibitors in sarcoma treatment. What is more, we describe and discuss the possibility and biological rationale for combination therapies with conventional treatments, target therapy and immunotherapy, highlighting potential avenues for future research to integrate CDK inhibition in sarcoma treatment.